Project-based learning: Mencapai Tujuan Kurikulum melalui Proyek Penguatan Profil Pelajar Pancasila di Sekolah Dasar - Havifa Nurhijatina; Nabila Joti Larasati; Zulhijrah Zulhijrah; M. Ferry Irawan; Andi Prastowo (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
The factors causing the low quality of education in Indonesia are largely attributed to the disproportionate role given to schools, the lack of adequate learning planning, the implementation of learning that is not optimal, the ineffective management of the curriculum system, and the application of learning outcome measurements that focus on cognitive aspects. This study aims to describe the implementation of project-based learning in supporting the achievement of curriculum objectives in the Pancasila profile strengthening project at Samirono State Elementary School, Yogyakarta Special Region. The approach in this research uses qualitative with case study method. The data sources in this research are primary data and secondary data using observation, interviews and documentation as data collection techniques. The technique to ensure data validity is using data triangulation. While the data analysis technique uses the Miles and Huberman model which goes through three stages, namely data collection, data reduction and data presentation. The result of this study is the implementation of project-based learning is an appropriate learning model to achieve curriculum objectives related to the development of potential and the development of Pancasila student profiles.